Persistent Methicillin-Susceptible Bacteremia Rapidly Cleared with Cefazolin and Ertapenem Combination Therapy in a Patient with COVID-19 - Ilges, Dan; Krishnan, Gayathri; Geng, Elvin (Case Reports in Infectious Diseases, 2022)
Methicillin-susceptible Staphylococcus aureus (MSSA) bloodstream infections (BSIs) are associated with significant morbidity and mortality. MSSA BSIs can rapidly disseminate, resulting in deep-seated infections, prolonged durations of bacteremia, and further metastases. Recently, cefazolin and ertapenem combination therapy has emerged as a potential therapeutic strategy to sterilize the blood in patients with persistent MSSA bacteremia. Here, we present a patient with COVID-19 pneumonia and concomitant MSSA BSI achieving blood culture sterilization within 24 hours of cefazolin and ertapenem combination therapy initiation following 11 days of positive blood cultures.